Evaluation of Urban Transformation in Building Scale in Terms of Social Sustainability: Goztepe Case - Cetin, Reycan (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
In this study, the social sustainability framework and the transformation processes realized in Kadikoy district of Istanbul were examined. Processes covering the general aspect of district have been discussed in detail in the context of social sustainability and related concepts of changing housing profile typology, the effects of street perception on identity, the effects of transformation on building quality on the quality of life and the change of the profile of urban residents in the neighborhood in terms of social sustainability.
Keywords: Social sustainability; Neighborhood; Identity; Sustainable community; Science & Technology - Other Topics; Engineering